MANAJEMEN REKRUTMEN DAN RETENSI PENDIDIK BERBASIS NILAI-NILAI ISLAM (ISLAMIC HUMAN CAPITAL MANAGEMENT) - Nur Azizeh (STKIP Pesisir Selatan, 2026)
Many Islamic educational institutions face high teacher turnover rates due to conventional recruitment practices that ignore spiritual dimensions and retention schemes that focus solely on materialistic-transactional aspects. This study aims to analyze and formulate an Islamic Human Capital Management (IHCM) model for recruiting and retaining educators based on Islamic values (amanah, itqan, and ikhlas). Using a descriptive-qualitative approach based on an integrative literature review, the data corpus was gathered from reputable databases (Scopus, WoS, SINTA) covering the 2021–2026 period and analyzed through content and thematic analysis. The findings reveal that integrating values into the Person-Organization Value Fit (P-O Fit) selection instruments effectively screens spiritual competence and prevents value dissonance at an early stage. Furthermore, retention is strengthened through a holistic Spiritual Reward System (ruhaniyah, fikriyah, jasmaniyah) and a work climate of ukhuwah islamiyah that fosters deep affective commitment. It is concretely recommended for school administrators and educational foundations to develop interview selection rubrics based on ethical dilemmas, provide structured non-material incentives such as umrah programs and Islamic study sessions, and establish sharia-compliant fair wage standards to maintain educator loyalty.